Mediating effects of social capital and grocery stores on obesity rates in rural food deserts - Menefee, Daja C. (Kansas State University, 2013)
Over the past few decades, the prevalence of obesity and diet-related diseases has steadily increased and become a major public health concern. Part of the problem has been attributed to the large quantity of unhealthy (energy-dense) foods U.S. consumers include in their diets. Statistics on food environment suggest that some areas and households have easier access to fast food restaurants and convenience stores but limited access to supermarkets. Limited access to nutritious food and relatively easier access to less nutritious food have been shown to lead to poor diets and, ultimately, to obesity and diet-related diseases. These issues may more negatively affect some communities than others, particularly rural communities as they tend to be further away from food outlets compared to urban areas. Counties are classified as food deserts based upon the percentage of residents living below the federal poverty line and the percentage of residents residing more than one mile from a supermarket. This definition excludes many viable food outlet options, including smaller independently-owned groceries. With rural residents being at a greater disadvantage, it becomes important to consider smaller groceries as an alternative for these communities. The level of social capital may be an indicator of an area’s willingness to support its community. The social environment of rural communities can be characterized as having a high degree of interconnectedness within the community, so that “everybody knows everybody else” (Beggs, Haines, & Hurlbert, 1996). This unique social network in rural communities facilitates the buildup of social capital, which incorporates reciprocity and the willingness to do things for members within the network. This study finds a negative relationship between obesity and social capital in nonmetropolitan counties, as well as a negative relationship between obesity rates and rural grocery stores. These conclusions lend insight into ways to decrease the level of obesity in rural areas.
Keywords: Obesity; Rural grocery stores; Social capital; Agriculture, General (0473)